Determining the Trace concentration of some heavy metal elements in Dusky spinefoot, Siganus luridus, in the marine waters of Tartous - صــلاح رائـدة; محمد حسن; علي سلطانة; غياث عباس (Latakia University Journal -Biological Sciences Series, 2022)
Contamination of fish with heavy metals is an important indicator of the pollution of the environment in which it lives, and the possibility of its transmission within the food chain down to humans. This research aimed at determining the concentration of four heavy metal elements (Zn, Cu, Pb, and Cd) in the muscles (consumable part) of Siganus luridus fish, caught from the beach of Banias city, for two consecutive years, from March 2019 to February 2021. Tests for the detection of this metal were carried out using atomic absorption spectroscopy, according to the techniques of electrothermal and flame ablation. The results of the study showed a higher concentration of heavy metals in the muscles of Siganus luridus in the estuary area of ​​the Jobar River than in the other two sites, followed by the Banias River estuary area, and then the Al-Basiya area, where the average rates of the concentrations of these elements in all the studied sites during the study period ranged between (3.482-6.120 µg/g wet weight) for zinc, followed by copper with average concentrations ranging between (0.366-0.552 µg/g wet weight), then lead (0.0159-0.0249 µg/g wet weight), while cadmium was The least concentrated (0.005-0.008 µg/g wet weight), but all of these concentrations were within the limits allowed by the Food and Agriculture Organization of the World, and therefore they do not pose a threat to human health, as the final consumer.